Islamic Education Quality from an Islamic Perspective: An Analysis of Improvement Strategies - Nikmatul Khoiriah; Bedjo Sujanto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Global challenges and changes in social values require Islamic educational institutions to produce graduates with critical and creative thinking skills to compete amid the currents of modernization and digitalization. However, the quality of education is not measured solely by academic standards, but also by spiritual, moral, social, and managerial dimensions that reflect the unity of faith, knowledge, and charity. This study aims to analyze the concept of educational quality from an Islamic perspective and formulate a strategy for comprehensively improving the quality of Islamic educational institutions. This study uses a qualitative-descriptive approach based on library research, analyzing primary sources such as the Qur'an, hadith, and tafsir, as well as modern scientific literature on Islamic educational quality management. The results show that the quality of Islamic education is built on the principles of tauhid, amanah, adl, ihsan, and itqan, which guide all educational activities towards the formation of a perfect human being. Quality improvement strategies include strengthening teachers' competence and spirituality, curriculum innovation grounded in Islamic values and the needs of the times, implementing Islamic quality management, and the ethical use of digital technology. Thus, the quality of Islamic education is an integrative process that combines spiritual, professional, and adaptive dimensions to realize quality education, character, and global competitiveness.